Produtividade do trabalho das cadeias produtivas da indústria de transformaç\~ao brasileira no período 2000-2019 - Luiz Dias Bahia (Instituto de Pesquisa Econômica Aplicada (IPEA), 2023)
– The present work seeks to measure for the period 2000-2019 the evolution of sectoral work productivity in production chains. To do so, we carried out an input-output matrix (IPM) exercise based on the Brazilian Annual National Accounts from 2000 to 2019 (which are currently available). In the analyzed period as a whole, we verified a tendency of productivity stagnation, with more positive results of the agro-industrial complex and less expressive of the textile complex. Faced with the productive horizon of advanced manufacturing, which is very capital intensive, the manufacturing industry has not yet found a new growth pattern capable of reversing the inexpressive path observed mainly in the period 2014-2016, in order to make productive transformation feasible implicit in advanced manufacturing.
Keywords: J24; L6; 330; labor productivity; manufacturing